It's Pumpkin Day, Mouse! - Numeroff, Laura Joffe; Bond, Felicia (New York : Balzer + Bray, 2021)
Mouse paints each pumpkin with a different face.
On board pages.
AD 380
Accelerated Reader
Keywords: Pumpkin -- Juvenile fiction; Mice -- Juvenile fiction; Jack-o-lanterns -- Juvenile fiction